Superparamagnetic Oxygen-Loaded Nanobubbles to Enhance Tumor Oxygenation During Hyperthermia - Zullino, Sara; Argenziano, Monica; Ansari, Shoeb; Ciprian, Roberta; Nasi, Lucia; Albertini, Franca; Cavalli, Roberta; Guiot, Caterina (Frontiers in Pharmacology, 2019)
Tumor oxygenation is a critical issue for enhancing radiotherapy (RT) effectiveness. Alternating RT with hyperthermia improves tumor radiosensitivity by inducing a massive vasodilation of the neoangiogenic vasculature provided the whole tumor is properly heated. The aim of this work was to develop superparamagnetic oxygen-loaded nanobubbles (MOLNBs) as innovative theranostic hyperthermic agents to potentiate tumor oxygenation by direct intracellular oxygen administration. Magnetic oxygen-loaded nanobubbles were obtained by functionalizing dextran-shelled and perfluoropentane-cored nanobubbles with superparamagnetic iron oxide nanoparticles. Magnetic oxygen-loaded nanobubbles with sizes of about 380 nm were manufactured, and they were able to store oxygen and in vitro release it with prolonged kinetics. In vitro investigation showed that MOLNBs can increase tissue temperature when exposed to radiofrequency magnetic fields. Moreover, they are easily internalized by tumor cells, herein releasing oxygen with a sustained kinetics. In conclusion, MOLNBs can be considered a multimodal theranostic platform since, beyond their nature of contrast agent for magnetic resonance imaging due to magnetic characteristics, they showed echogenic properties and can be visualized using medical ultrasound.